2015
DOI: 10.1259/bjr.20140282
|View full text |Cite
|
Sign up to set email alerts
|

Advances in MRI for the evaluation of carotid atherosclerosis

Abstract: Carotid artery atherosclerosis is an important source of mortality and morbidity in the Western world with significant socioeconomic implications. The quest for the early identification of the vulnerable carotid plaque is already in its third decade and traditional measures, such as the sonographic degree of stenosis, are not selective enough to distinguish those who would really benefit from a carotid endarterectomy. MRI of the carotid plaque enables the visualization of plaque composition and specific plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…[17-19] In this study we found pre-operative cerebral arteriogram as the only imaging modality correlating with LOS. Yet, only 5% of patients underwent arteriogram and on review of the cases they were patients referred from neurology with complex intracranial and extracranial cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 80%
“…[17-19] In this study we found pre-operative cerebral arteriogram as the only imaging modality correlating with LOS. Yet, only 5% of patients underwent arteriogram and on review of the cases they were patients referred from neurology with complex intracranial and extracranial cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, also in the pathogenesis of peripheral ( i.e. , outside the central nervous system) macroangiopathic atherosclerosis, various immune cells are involved [ 41 , 42 , 43 ] and there is ongoing effort for in vivo visualization of atherosclerotic plaque composition [ 44 , 45 ]. Importantly, and in contrast to Niesten and co-workers [ 12 ] who reported AIS subtype-specific differences regarding the percentage of RBC infiltration, we found no differences in immune cell infiltration within the clots when having a detailed look at AIS subtypes according to TOAST criteria.…”
Section: Discussionmentioning
confidence: 99%
“…17 High-resolution carotid plaque MRI 18,19 is a technique that enables more detailed characterization of plaque composition than CTA, with identification of vulnerable plaque features such as intraplaque hemorrhage, lipid-rich necrotic core, and thinned or disrupted fibrous cap. [20][21][22] A study 23 using high-resolution MRI to examine nonstenotic carotid plaque in a smaller series of patients with cryptogenic stroke found high-risk imaging features indicative of type VI plaque (American Heart Association 24 ) in 38% (12/32) of carotid arteries ipsilateral to ischemic stroke, and no type VI plaque on the contralateral side. The absence of high-risk plaque on the contralateral side differs from our study, which found bilateral plaque $3 mm in 15% of patients with ESUS, and bilateral plaque $4 mm in 5% of patients.…”
mentioning
confidence: 99%